Poncet rheumatism secondary to ceco-appendicular tuberculosis in systemic lupus erythematosus - Abir Derbel; Mouna Snoussi; Amine Zouari; Mayeda ben Hamad; Raida ben Salah; Chifa Damak; Faten Frikha; Sameh Marzouk; Wiem Feki; Zouhir Bahloul (Romanian Journal of Infectious Diseases)
Background. Poncet’s rheumatism (RP) is an aseptic reactive arthritis secondary to active tuberculosis. Systemic lupus erythematosus (SLE) and tuberculosis are intricately related with an increase in the risk of tuberculosis in SLE. We present an original case of Poncet’s disease secondary to appendicular tuberculosis in patient with lupus disease. Case report. A 36-year-old female was followed in internal medicine for systemic lupus. In September 2023, she suffered from digestive complaints and polyarthritis. Infectious investigation and microbiologic study of joint fluid was negative. She had tenderness on pressure on the right iliac fossa. The computed tomography (CT) found an appendicular mucocele. She underwent laparotomy with right colectomy. Macroscopic aspect revealed tumorous lesion suggestive for malignancy. Histological study concluded to granulomatous inflammation with epithelioid and gigantocellular granulomas with anhist necrosis. Ceco-appendicular tuberculosis was retained. The patient received the anti-tuberculosis therapy with good progress. Conclusions. Early recognition of atypical location of tuberculosis leads to initiate appropriate treatment especially in immune compromise statue patient.